2022
DOI: 10.3122/jabfm.2022.04.210399
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Increase Colorectal Cancer Screening Uptake in Primary Care: A Systematic Review

Abstract: Objective: We systematically reviewed and summarized previous studies that examined facilitators and barriers to implementing interventions to increase CRCS uptake in primary care practice.Methods: We searched PubMed, Medline (EBSCO), and CINAHL databases, from the inception of these databases to April 2020. The search strategy combined a set of terms related to facilitators/barriers, intervention implementation, CRCS, and uptake/participation. A priori set inclusion and exclusion criteria were used during bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Therefore, the healthcare authorities should emphasize the role of GPs in enhancing CRC screening rates. A recent systematic review investigated the facilitators and barriers to implementing interventions to enhance CRC screening uptake in primary care practice ( Adhikari et al, 2022 ). In that study, the authors found that engagement of the clinic team, leadership team, and partners were the most critical implementation facilitators.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the healthcare authorities should emphasize the role of GPs in enhancing CRC screening rates. A recent systematic review investigated the facilitators and barriers to implementing interventions to enhance CRC screening uptake in primary care practice ( Adhikari et al, 2022 ). In that study, the authors found that engagement of the clinic team, leadership team, and partners were the most critical implementation facilitators.…”
Section: Discussionmentioning
confidence: 99%
“… 17–19 A recent systematic review reports that many of the existing studies had limited use of implementation science frameworks to guide a comprehensive theory and/or evidence-based understanding of the implementation factors specific to CRC screening interventions in primary care. 20 …”
Section: Introductionmentioning
confidence: 99%
“…For example, there have been general reviews published on interventions for screening uptake, 19 21 those focused on a specific cancer type only, 20 22–24 26 those focused on a specific type of intervention, 22 25 those focused on a specific population 24 or those in a primary care setting but without an equity focus. 26 Given that physician recommendation is one of the strongest and most consistent predictors of screening uptake, 27 28 a closer look at primary care provider (PCP) interventions for cancer screening is warranted. Moreover, much of the prior work published has focused on those who are eligible for screening broadly and not specifically on patients experiencing marginalisation.…”
Section: Introductionmentioning
confidence: 99%
“…While previous reviews on interventions aimed at increasing screening uptake have been published,19–26 none have focused specifically on our topic. For example, there have been general reviews published on interventions for screening uptake,19 21 those focused on a specific cancer type only,20 22–24 26 those focused on a specific type of intervention,22 25 those focused on a specific population24 or those in a primary care setting but without an equity focus 26. Given that physician recommendation is one of the strongest and most consistent predictors of screening uptake,27 28 a closer look at primary care provider (PCP) interventions for cancer screening is warranted.…”
Section: Introductionmentioning
confidence: 99%